Avaliação de métodos intermediários de irrigação para evitar a formação de smear-layer química - Silva, Camilla Corrêa (2016)
The aim of the present study was to evaluate the influence of three different intermediate irrigation protocols on the formation of chemical smear layer (CSL). Thirty freshly extracted human teeth were instrumented using R40 reciprocating files and irrigated with 5.25% NaOCl. Then, teeth were randomly divided into three groups (n=10), according to the intermediate irrigation protocol: Conventional irrigation with saline solution; Self-Adjusting File with saline solution; or EndoVac irrigation with saline solution. Then, the root canals were irrigated with 17% EDTA and received a final flush of 2% Chlorhexidine. After chemomechanical preparation, all specimens were sectioned and processed for observation of the CSL formation by using scanning electron microscopy (SEM). Two calibrated evaluators attributed scores to each specimen. The differences between activation protocols were analyzed with Kruskal-Wallis and Mann-Whitney U tests. Friedman and Wilcoxon signed rank tests were used for comparison between each root canal third. The results demonstrated that the use of Self-Adjusting File results in lower CSL formation when compared to Conventional and EndoVac irrigation (P<0.05). In the Conventional and EndoVac irrigation groups, cervical and medium thirds presented lower CSL formation when compared to the apical third (P<0.05). In the Self-Adjusting File groups no statistically significant differences were observed among the different root canal thirds (P>0.05). It can be concluded that the use of an intermediate irrigation with Self-Adjusting File avoids the formation of chemical smear layer.